Assessment of the impacts of atmospheric acid deposition on water quality and evaluate NBS counter-measures for La Buong river of Vietnam - Pandey, Santosh; Ho Huu Loc; Shanmugam, Mohana Sundaram; Kim Oanh Nguyen Thi; Sarawut Ninsawat; Asian Institute of Technology Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2022)
Water quality impacts from the atmospheric deposition is a current issue of South-East Asia. Rapid development consumes excessive fossil fuels which is main source that emits Sulfates and Nitrates which are transformed in the atmosphere and deposited to earth surface in dry and wet form. Wet deposition of atmospheric Nitrate and Sulfates when becomes acidic and impacts the surface water, terrestrial and aquatic ecosystem. This study uses the numerical model PCSWMM to assess the effects of monthly atmospheric acid deposition on 33 sub-catchments on the water quality of Vietnam's La La Buong River in the base year of 2018. To identify the important contributor of Nitrate and Sulfate concentration to impact the river's water quality, sensitivity analysis in each sub-catchment was performed. To demonstrate the various mitigation scenarios, NBS were artificially applied and evaluated. One rainfall used across the entire catchment, atmospheric deposition fluxes of NOx and SOx from the WRF-CAMx model were used as the model's inputs. Evaluation reveals that during rainfall, 84.94% of NOx and 94.41% of the SOx become wash off from total buildup loads. The contribution from atmospheric Nitrates concentration to the total measured Nitrate concentration was 20 to 30%. The average concentrations at OFs were determined to be 1.29, 1.57, and 1.72mg/l, respectively, below threshold of QCVN 08-MT:2015/BTNMT Class A2; 5.35mg/l. Sensitivity analysis shows proportion of Grassland is the most sensitive land use. Three LIDs; Vegetative Swale, Infiltration Trenches, and Bio-Retention Cells. were designed and jointly applied for 10%, 15% and 20% LID catchment coverage OF1, OF2 and OF3. These scenarios reduced simulated unmitigated contribution up to 31%, 35% and 39% for Nitrate deposition and 29%, 33% and 37% for Sulfate deposition. This research recommends to policy makers to consider NBS when designing a future management plan in association to application of control measures for pollutants in the system
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Water Engineering and Management
Thesis (M. Eng.) - Asian Institute of Technology, 2022
Keywords: Water quality -- Vietnam; Atmospheric deposition -- Vietnam